AIAA Atmospheric Flight Mechanics Conference 2012
DOI: 10.2514/6.2012-4404
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Model Reduction for Flexible Aircraft Control Design

Abstract: The paper describes a systematic approach to the model reduction of large dimension fluid-structure-flight models, and the subsequent flight control design of very flexible aircraft. System nonlinearities may be due to the large wing deformations, the coupling between flexible and rigid body dynamics and/or flow separation at large angles of incidence. A nonlinear reduced order model is used to reduce the computational cost and dimension of the large-order nonlinear system for a practical control law design. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…The paper expands on previous work, 13 where the model reduction was applied to different test cases with a range of nonlinearities in both fluid and structural models and it was shown that control problem is possible on the reduced models generated. This paper demonstrates the use of the model reduction for a full-scale flexible unmanned aerial vehicle (UAV) interacting with gust and using control surfaces for loads alleviation.…”
Section: Introductionmentioning
confidence: 76%
“…The paper expands on previous work, 13 where the model reduction was applied to different test cases with a range of nonlinearities in both fluid and structural models and it was shown that control problem is possible on the reduced models generated. This paper demonstrates the use of the model reduction for a full-scale flexible unmanned aerial vehicle (UAV) interacting with gust and using control surfaces for loads alleviation.…”
Section: Introductionmentioning
confidence: 76%
“…In the following results, the Schur complement form of the eigenvalue problem presented by Badcock and Woodgate 26 is used to track the migration of the three structural eigenvalues with the reduced velocity. The first comparison is made with a two degree-of-freedom (DoF) aerofoil model presented by Alighanbari and Price 27 as well as the original two degree-of-freedom model by Da Ronch et al 28 Since this specific comparison is made between a three degree-of-freedom and a two degree-of-freedom model, it is necessary to enforce a very high stiffness in the flap degree of freedom by setting a high value of ω 2 . This effectively limits the dynamics of the three degree-of-freedom model to a two degree-of-freedom system.…”
Section: Validationmentioning
confidence: 99%
“…The coupled full order model follows the formulation presented in. 1 Results are obtained using two-noded displacement-based elements. In a displacement-based formulation, dominant nonlinearities arising from large deformations are cubic terms, as opposed to an intrinsic description where they appear up to second order.…”
Section: Geometrically-nonlinear Flexible Wingmentioning
confidence: 99%
See 1 more Smart Citation
“…Right and left eigenvectors are scaled to satisfy the biorthonormality condition,see . 10 The projection of the full order model is done using a transformation of coordinates ∆w = Φ z +Φz…”
Section: Nonlinear Model Order Reductionmentioning
confidence: 99%